Implementation of the Four Pillars of Nationality in the Formation of the Character of Students - Ahsena Lutfi Afifah; Endang Ekowati; Tamyis Tamyis (Global Education Journal, 2026)
Character education is a strategic issue in the development of the Indonesian nation amidst the currents of globalization, the development of digital technology, and increasingly complex social changes. This study aims to describe the implementation of the Four National Pillars in shaping students' character, analyze the strategies for internalizing national values, and identify the supporting and inhibiting factors in their implementation at Pondok Pesantren Hidayatul Mubtadiin Sidoharjo Jati Agung South Lampung in 2025. This study employed a qualitative approach with a field research design. Data were collected through observation, in-depth interviews, and documentation. The research informants consisted of the Islamic boarding school leaders, Islamic teachers, student organization administrators, and students. Data analysis used the Miles and Huberman interactive model, including data reduction, data display, and conclusion drawing, while data validity was ensured through source, technique, and time triangulation. The results showed that the implementation of the Four National Pillars was carried out through learning activities, habituation, role modeling, student organizations, social activities, and daily pesantren culture, which successfully formed religious, disciplined, tolerant, responsible, patriotic, and unity-oriented characters among students. The study concludes that the implementation of the Four National Pillars in Islamic boarding schools plays a significant role in shaping students into religious, nationalistic, moderate, and morally upright individuals through the integration of national values ​​into all educational and daily life activities within the Islamic boarding school environment.